Penggunaan Media Interaktif Berbasis PowerPoint dalam Meningkatkan Motivasi Belajar PPKn Siswa kelas IV MIS Yasim Pesa - Nurlailah, Nurlailah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) STIT Sunan Giri Bima, 2024)
This study aims to determine the effectiveness of using PowerPoint-based interactive media in increasing student learning motivation in Pancasila and Civics Education (PPKn) subjects at MIS Yasim Pesa. The background of this study is the low motivation of students to learn which can be seen from the lack of active participation, lack of curiosity, and boredom when taking Civics lessons. This study used the Classroom Action Research (PTK) method which was carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The research subjects were MIS Yasim Pesa fourth grade students totaling 20 people. Data collection techniques were carried out through observation, questionnaire learning motivation, and documentation. The results showed that the use of interactive PowerPoint media can increase students' learning motivation. This is evidenced by the increase in the average score of the motivation questionnaire from 68% in cycle I to 85% in cycle II. Thus, PowerPoint-based interactive media is effective in increasing student learning motivation in Civics learning.